PENGARUH SKILL, PENGETAHUAN, DAN KARAKTERISTIK TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENEMPUH PENDIDIKAN PROFESI AKUNTANSI - Tika Ratnawati; Sumaryanto Sumaryanto (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
Professional education is organized additional education after studying Strata one with intent to obtain a degree accountant, which aims to produce graduates who master the skill of the accounting profession and provide professional accounting competence. The main causes of accounting graduate students want to go to the Accounting Profession (PPAK) due to the various motivations they have. The purpose of this research is to investigate the influence of skills, knowledge, and characteristics of students interest in accounting for the accounting profession was educated at the University of Ahmad Dahlan Yogyakarta. Samples taken in this study using purposive sampling of students majoring in accounting semester V and VII, which already took a course auditing. The sample in this study 137 respondents Ahmad Dahlan University students. Variable are of interest to accounting students studying accountancy profession, skill, knowledge, and characteristics. Analysis using multiple regression analysis technique. Results of multiple regression analysis shows the level of the coefficient of determination (adjusted R2) of 0.050. This is the high percentage of variable skill, knowledge, and characteristics in explaining the variables of interest to accounting students studying accountancy profession at 5% and the remaining 95% is explained by variables or other factors outside the study. Based on the regression F test to prove that there skiil influence, knowledge, and characteristics significantly to the interest of students studying accounting for the accounting profession is shown by the F probability value <Î± (0.05). Testing individuals (t test on regression) provide empirical evidence that the skills and knowledge that do not affect the interest of students to study accountancy profession dedicated to the probability value t> Î± (0.05), whereas only characteristics affect student interest in accounting for studying the accounting profession is shown by the probability value t> Î± (0.05).